2016
DOI: 10.1177/1937586716672041
|View full text |Cite
|
Sign up to set email alerts
|

On the Planning and Design of Hospital Circulation Zones

Abstract: Several knowledge gaps as well as commonalities in the pertinent research literature were identified. Perhaps the overriding finding is that occupants' meaningful exposure to views of nature from within hospital circulation zones can potentially enhance wayfinding and spatial navigation. Future research priories on this subject are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…However, guiding patients' families to destinations was perceived as a frustrating, distracting, and waste of time and steps (Buffoli et al, 2016). As suggested by previous research (Jiang & Verderber, 2017;Mustikawati et al, 2017;Pati, Harvey, Willis, et al, 2015), participants recommended implementing meaningful visual cues and eye-level signage to improve wayfinding experiences. These findings reflect the importance of spatial sequences and ER configurations that afford direct access to destinations enhances wayfinding and movement patterns.…”
Section: Wayfindingmentioning
confidence: 89%
See 1 more Smart Citation
“…However, guiding patients' families to destinations was perceived as a frustrating, distracting, and waste of time and steps (Buffoli et al, 2016). As suggested by previous research (Jiang & Verderber, 2017;Mustikawati et al, 2017;Pati, Harvey, Willis, et al, 2015), participants recommended implementing meaningful visual cues and eye-level signage to improve wayfinding experiences. These findings reflect the importance of spatial sequences and ER configurations that afford direct access to destinations enhances wayfinding and movement patterns.…”
Section: Wayfindingmentioning
confidence: 89%
“…Ineffective wayfinding and signage causes inefficiency and workplace stress among healthcare providers. Without clear directional signage, patients may wander, become aggressive, fatigued, and abusive to providers (Jiang & Verderber, 2017;Pati, Harvey, Willis, et al, 2015). Nevertheless, there is a lack of empirical research on the impact of navigation and wayfinding qualities in hospital-based ED facilities.…”
Section: Wayfindingmentioning
confidence: 99%
“…Knowledge from evidence-based health care design has grown rapidly in the last decade, supporting the argument that more knowledge is needed about the effect of the design of the birth environment and design in hospitals in general [ 14 , 15 ]. Research from Australia and England have shown that the birth environment does not only have an impact on the birth experience and birth outcomes for women and neonates, but also on the woman's birth supporters and maternity care staff [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…A simple building that is easy to navigate enhances occupants' satisfaction, optimizes logistics, and reduces the risk of falls in fragile people [52]. This is challenging in complex healthcare facilities; therefore, wayfinding strategies have to be adopted [26].…”
Section: Wayfinding Featuresmentioning
confidence: 99%